Defining optimal dosing of ciprofloxacin in patients with septic shock. (26th February 2019) - Roberts, Jason A; Alobaid, Abdulaziz S; Wallis, Steven C; Perner, Anders; Lipman, Jeffrey; Sjövall, Fredrik
Abstract: Background: Patients with septic shock may undergo extensive physiological alterations that can alter antibiotic pharmacokinetics. Objectives: To describe the population pharmacokinetics of ciprofloxacin in septic shock and to define recommendations for effective ciprofloxacin dosing in these patients. Methods: Adult patients with septic shock treated with ciprofloxacin were eligible for inclusion. Concentrations were measured by HPLC-MS/MS. Population pharmacokinetic modelling was performed with Monte Carlo simulations then used to define dosing regimens that optimize the PTA of an AUC/MIC ratio >125 for different MICs and fractional target attainment (FTA) of empirical and targeted therapy against Pseudomonas aeruginosa . Results: We included 48 patients with median Simplified Acute Physiology Score (SAPS) II of 49 and 90 day mortality of 33%. Ciprofloxacin pharmacokinetics was best described by a two-compartment linear model including CLCR and body weight as covariates on CL and central volume respectively. With a dose of 400 mg q8h and CLCR of 80 mL/min, >95% PTA was achieved for bacteria with MICs ≤0.25 mg/L. For empirical treatment of P. aeruginosa, 600 mg q8h only reached a maximum of 68% FTA. For directed therapy against P. aeruginosa, a dose of 600 mg q8h was needed to achieve sufficient AUC/MIC ratios. Conclusions: In patients with septic shock, standard ciprofloxacin dosing achieved concentrations to successfully treat bacteria with MICs ≤0.25 mg/L and then only in patients with normal or reduced CLCR . To cover pathogens with higher MICs or in patients with augmented renal CL, doses may have to be increased.